Health Equity and Financial Protection in Zambia - World Bank (Washington, DC, 2017)
This report analyzes equity and financial protection in the health sector of Zambia. In particular, it examines inequalities in health outcomes, health behavior and health care utilization; benefit incidence analysis; financial protection; and the progressivity of health care financing. Data are drawn from the 2007 Zambia demographic and health survey, the 2006 Zambia living conditions monitoring survey, the 2003 Zambia world health survey and the 2003 Zambia national health accounts. All analyses are conducted using original survey data and employ the health modules of the ADePT software. Overall, health care financing in Zambia in 2006 was fairly progressive, i.e. the better-off spent a larger fraction of their consumption on health care than the poor. The financing sources that contribute to the overall progressivity of health care finance are general taxation, which finances 42 per cent of domestic spending on health, and contributions made by private employers, which finance 9 per cent of spending. An additional contribution to overall progressivity is made through pre-payment mechanisms, but this remains fairly limited given that they only represent 1 per cent of total health finance. Out-of-pocket health payments, which account for 47 per cent of total health financing, appear to be proportional to income, with only slight and not statistically significant evidence of progressivity.